1995
DOI: 10.1002/eji.1830250218
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of the interferon‐γ gene correlates with its expression by primary T‐lineage cells

Abstract: To determine the potential role of methylation in the regulation of interferon-gamma (IFN-gamma) gene transcription by T cells, primary T-lineage cell populations were analyzed for the extent of methylation of three CpG sites within or near transcriptional activator elements in the 5' flank and first intron of the human IFN-gamma gene. A striking correlation was observed between the capacity of the IFN-gamma gene to be expressed and the degree of hypomethylation. The IFN-gamma gene was virtually completely met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
2
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 31 publications
6
66
2
1
Order By: Relevance
“…Previous studies using methylation-sensitive restriction mapping have investigated the status of the Ϫ54 CpG site in human CD4 ϩ and CD8 ϩ T cells (18,23). We have extended these studies by the use of a sensitive bisulfite sequencing technique that allows measurement of methylated cytosine in any context over a DNA region of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using methylation-sensitive restriction mapping have investigated the status of the Ϫ54 CpG site in human CD4 ϩ and CD8 ϩ T cells (18,23). We have extended these studies by the use of a sensitive bisulfite sequencing technique that allows measurement of methylated cytosine in any context over a DNA region of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of 500 ng plasmid DNA was performed with T7 primer (5Ј-TAA TAC GAC TCA CTA TAG GG) and BigDye Terminator Ready Reaction Mix (PE Applied Biosystems, Foster City, CA) according to the manufacturer's instructions, except that the cycle-sequencing PCR parameters were varied to compensate for AT-rich bisulfite-treated DNA using an annealing temperature of 45°C and extension at 55°C. (18,23), and, conversely, a hypermethylated IFN-␥ promoter can disrupt nuclear factor binding (17,24). The positions of CpG sites that, when methylated, may be potentially disruptive to nuclear factor binding are identified in Fig.…”
Section: Bisulfite Treatment Pcr and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other reports have shown that epigenetic mechanisms involving DNA methylation and/or chromatin conformation are key features of IFN-␥, IL-2, IL-3, and IL-4 expression in T cells [53][54][55][56][57][58][59]. In the case of the IL-2 and IL-4 genes, epigenetic mechanisms may allow differential regulation of individual alleles of the same cytokine gene in single T cells [60][61][62][63].…”
Section: Intrinsic Properties Of the Responding T Cellsmentioning
confidence: 99%
“…11,[13][14][15]22 Studies by other groups have indicated that regulation of IFN-g gene expression in primary T cells differs from that observed in tumor T-cell lines, and likewise, differs in naïve compared to memory T-cell subsets. [23][24][25] Differential cytokine gene regulation may be controlled, in part, Novel ERE-like cis-element in IFNG promoter R Gonsky et al by DNA methylation patterns. The increased IFN-g expression in Th0 or Th1, compared to Th2, cells is correlated with the hypomethylated status of IFNG.…”
Section: Discussionmentioning
confidence: 99%